Polydatin reduces Staphylococcus aureus lipoteichoic acid‐induced injury by attenuating reactive oxygen species generation and TLR2‐NFκB signalling. Issue 11 (19th May 2017) - Zhao, Gan; Jiang, Kangfeng; Wu, Haichong; Qiu, Changwei; Deng, Ganzhen; Peng, Xiuli
Abstract: Staphylococcus aureus ( S. aureus ) causes severe inflammation in various infectious diseases, leading to high mortality. The clinical application of antibiotics has gained a significant curative effect. However, it has led to the emergence of various resistant bacteria. Therefore, in this study, we investigated the protective effect of polydatin (PD), a traditional Chinese medicine extract, on S. aureus lipoteichoic acid (LTA)‐induced injury in vitro and in vivo . First, a significant improvement in the pathological conditions of PD in vivo was observed, suggesting that PD had a certain protective effect on LTA‐induced injury in a mouse model. To further explore the underlying mechanisms of this protective effect of PD, LTA‐induced murine macrophages were used in this study. The results have shown that PD could reduce the NF‐κB p65, and IκBα phosphorylation levels increased by LTA, resulting in a decrease in the transcription of pro‐inflammatory factors, such as TNF‐α, IL‐1β and IL‐6. However, LTA can not only activate NF‐κB through the recognition of TLR2 but also increase the level of intracellular reactive oxygen species (ROS), thereby activating NF‐κB signalling. We also detected high levels of ROS that activate caspases 9 and 3 to induce apoptosis. In addition, using a specific NF‐κB inhibitor that could attenuate apoptosis, namely NF‐κB p65, acted as a pro‐apoptotic transcription factor in LTA‐induced murine macrophages. However, PD could inhibit the generation of ROS and NF‐κB p65 activation, suggesting that PD suppressed LTA‐induced injury by attenuating ROS generation and TLR2‐NFκB signalling.